IMPLEMENTASI KEBIJAKAN SERTIFIKASI GURU PADA SEKOLAH MENENGAH ATAS DI KOTA PALEMBANG - Isabella Isabella (UNIVERSITAS INDO GLOBAL MANDIRI, 2019)
The purpose of this research is to investigate the implementation of policies teacher certification in the senior high school in Palembang. Analysis of research is to use the theory of Edwards III who see through the implementation of a policy dimensions: communication, resources, disposition and bureaucratic structures. The method research used a qualitative descriptive analysis with a phenomenological approach. Techniques of data collection through in-depth interviews and check of documents. While the process of data analysis through data reduction, data and draw conclusions. The results showed that: Dissemination of certification information to teachers, only by phone, not by mail. In addition to the staff on duty to take care of the implementation of the certification has been no separation between levels of education, from elementary school teachers, to senior high school. Needed socialization into schools to information received by the school and by the rules more clearly defined certification committee.Kata kunci: Certification policies, teacher